Management of Earlobe Keloid by Triple Combination Therapy (Core Excision, Fillet Flap, and Intralesional Corticosteroids): A Case Report - Ammarilis Murastami; Pristia Widya Monica; Pratiwi Prasetya (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Keloid is a growing neoplasm characterized by the proliferation of benign fibroblasts. The chest, shoulders, head, especially the ear lobes, neck, arms, and upper back are the areas most commonly affected by keloids. The use of a fillet flap allows dissection of the keloid core and leaves loose skin for wound closure. This study aims to describe the surgical management of keloids in the auricular region using the core excision technique with a keloid fillet flap with a combination of corticosteroid injections. Case presentation: A 54-year-old man came with the main complaint of a red lump with hard consistency and itching on the right ear. The management of this patient was surgery using the core excision technique with a keloid fillet flap followed by intra-operative intralesional and immediate post-operative corticosteroid injection and then programmed for corticosteroid injection at the next follow-up. Post-operative therapy was given cefixime 2x100mg and oral analgesic mefenamic acid 3x500mg for 5 days. Conclusion: Keloid surgery is the treatment of choice because it produces good cosmetic results quickly. Routine follow-up and additional therapy are required to prevent a future post-operative recurrence.